On the Predictability of the Danish Equity Premium - Peter Møllegaard; Jochen Lorentzen (Copenhagen Business School (CBS), Department of Economics, 2001)
The paper analyses the extent of and the reasons behind limits to competition policy harmonisation in EU enlargement. Our focus is on vertical restraints. First, we compare the relevant legal regimes towards vertical agreements in the EU and in Eastern Europe. We then describe competition policy practice in all ten EU candidate countries and point out differences both between East and West and among the candidates. Finally, we use insights from case studies of subcontractor agreements in the Eastern Europe. to highlight instances of non-conformity between (1) East European competition law and practice and (2) EU rules and East European competition law enforcement. Our conclusion targets an underdeveloped competition culture as primary culprit for limits to effective – as opposed to merely legal – harmonisation of competition policy in the run-up to EU enlargement.
hdl:10398/7502
Keywords: A00; F00; 330; competition policy; EU; Eastern Europe